Escalation of commitment and CEO departures: theory and evidence - Chulkov, Dmitriy V.; Barron, John M. (Journal of Business Economics and Management, 2021)
The escalation of commitment process involves a decision-maker continuing commitment to an investment after receiving negative information. This study develops a principal-agent model to explore how escalation decisions are linked with departures of CEOs from the position.  With asymmetric information, a CEO has an incentive to conceal prior decision errors by escalating commitment to failing investments and leaving the firm before the outcome of investment decisions is disclosed publicly. Results of empirical analysis based on a sample of over 3,000 US firms are consistent with the theory and demonstrate that firms’ reporting of low financial performance relative to their industry as well as initiation of new discontinued operations are preceded, and not followed, by unplanned CEO departures.